El rol del Psicólogo en el contexto de aplicación de la nueva Ley Orgánica de Educación Intercultural en el Departamento de Consejería Estudiantil de la Unidad Educativa Cardenal Spellman - Martínez Vallejo, Mirian Amparo (2014)
The document makes a detailed review in relation to the changes and transformations produced among the Departments of Student´s Counseling throughout the country in all the levels and modalities which are now emerging as final outcomes in the general formative process of children and teenagers, and as a preventive role rather that a remedial one, for this, is a must to know and apply the rules describing how the student counseling should be understood, also the member´s profiles integrating this department plus the functions to be developed in each one of them in agreement with the general actions of the educative institution. It is worth to mention that the integral attention to the students, activities, and corresponding programs of this department must take into account the active participation of the entire staff as mentioned in the LOEI.